A molecular sensor to quantify the localization of proteins, DNA and nanoparticles in cells - Laura I. FitzGerald (Nature Portfolio, 2020)
Determining the trafficking of intracellular material is commonly done by colocalisation analysis using microscopy. Here the authors monitor trafficking of select cargo by measuring the conversion of quenched SNAP-tag substrates by subcellularly-localised SNAP-tag and detection by flow cytometry.